Youth Unemployment and EU: A Love-Hate Relationship - Varvaressos-Drosos, Theodore (HAPSc Policy Briefs Series, 2021)
Youth unemployment remains a key concern for the European Union’s member-states, especially the weakest, for at least 10 years. Although the European Union has taken initiatives in the past, young citizens throughout the European Union are still facing the serious problem of unemployment every day. And statistical findings do not look promising of a better or more steady future, even though EU is aiming to invest even more money in the field of youth employment. Therefore, the dynamic of youth unemployment is having a major socioeconomic consequence. This is the reason why realistic measures and initiatives need to be taken in order to avoid the repeat of 2008. Youth unemployment in the European Union as well as the measures and the initiatives that have been taken both during the Economic Crisis and the COVID-19 pandemic are being analysed in the current policy brief.